SCHEDULING WITH UNCERTAINTY - Luján Segura, Edwar (2015)
In real world, uncertainty is a important factor to take into account otherwise the schedules face the risk of failing, and/or to become unviable. Therefore, when creating schedules we must consider theuncertainty to prevent or repair the undesired effects. In this work we make a review of scheduling with uncertainty to respond the following questions: How can we represent the uncertainty? and What methodsdo exist to treat uncertainty? Likewise, we show the different ways in how the uncertainty is present in areas like the petrochemistry, the production, the transport, the energy, etc. We also make a study about two questions that all scheduling must respond: When to programme? and how to programme?